2021
DOI: 10.1097/hjh.0000000000003047
|View full text |Cite
|
Sign up to set email alerts
|

Incident aortic root dilatation in the general population: findings from the Pamela study

Abstract: We sought to assess the long-term changes in aortic root diameter in a population-based sample, focusing on new-onset aortic root dilatation, as well as on the demographic and clinical variables independently related to this dynamic process.Methods: A total of 1122 participants with measurable echocardiographic parameters at baseline and after a 10-year follow-up were included in the analysis. Sexspecific upper limits of normality for absolute aortic root diameter, aortic root diameter indexed to body surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It should be noted, however, that available evidence regarding dynamic changes over time in AR diameter in the community and in hypertensive cohorts suggests somewhat different conclusions from cross-sectional studies. Indeed, among the participants to the PAMELA study, the incidence of new AR dilatation over the 10-year follow-up period ranged from 3.4% (AR/BSA) to 4.4% (AR/height) (33). In difference, the Campania Salute Network study, including 4,856 hypertensive patients, showed that as many as 366 participants (11%) with normal AR diameter at baseline developed AR dilatation during a follow-up of 6 years (34).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that available evidence regarding dynamic changes over time in AR diameter in the community and in hypertensive cohorts suggests somewhat different conclusions from cross-sectional studies. Indeed, among the participants to the PAMELA study, the incidence of new AR dilatation over the 10-year follow-up period ranged from 3.4% (AR/BSA) to 4.4% (AR/height) (33). In difference, the Campania Salute Network study, including 4,856 hypertensive patients, showed that as many as 366 participants (11%) with normal AR diameter at baseline developed AR dilatation during a follow-up of 6 years (34).…”
Section: Discussionmentioning
confidence: 99%
“…The ARD prevalence in 1860 randomly selected healthy subjects from the general population of Monza (Milan, Italy), aged 25 to 74 years, ranged from 5.6% to 9.6%, indexed to the body surface area and height, respectively. Sex‐specific prevalence was slightly higher in men than women (Cuspidi, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the echocardiogram and electrocardiogram (ECG) findings in hEDS patients seen at the University of Miami. We compared our results with other studies on cardiac presentations of hEDS and published epidemiologic studies (Asher et al, 2018;Atzinger et al, 2011;Cuspidi et al, 2022) of MVP and ARD, on similar gender and age subjects in the general population. We aim to provide further evidence toward more defined and reliable diagnostic criteria and recommended monitoring.…”
mentioning
confidence: 92%
“…Parallel changes between proximal aortic dilatation and hypertensive target organ damage left ventricular hypertrophy and atrial fibrillation LVH is traditional hypertensive target organ damage and is associated with adverse cardiovascular outcomes. Crosssectional studies have witnessed a higher prevalence of LVH in hypertensive patients with proximal aortic dilation than their counterparts with normal proximal aorta (OR ¼ 2.4 for ascending aorta dilation [89], OR ¼ 3.1 for the aortic root dilation [10]). Moreover, the prevalence of LVH showed a stepwise increase with the aortic size tertile rising in a never treated hypertensive population [9].…”
Section: Clinical Significance Of Proximal Aorta Dilation In Hyperten...mentioning
confidence: 99%
“…Additionally, proximal aortic dilatation has been regarded as a morphological manifestation of vascular remodeling and is closely associated with traditional cardiovascular risk factors like left ventricular hypertrophy (LVH) and arteriosclerosis [1,[9][10][11][12]. However, the long-term prognostic value of proximal aortic dilatation has not been confirmed in hypertensive patients, which maybe one of the reasons why this indicator was not included as a risk stratification factor in current guidelines for hypertension [13,14].…”
Section: Introductionmentioning
confidence: 99%